Microsoft MS-100 certification : M365 identity and services - Hood, David (Skylines Academy, LLC, 2019)
"With the NEW MS-100 Certification Course: M365 Identity and Services, you'll be able to take and pass the MS-100 exam. The MS-100 exam, coupled with the MS-101 exam (course coming soon!), will award you the 'Microsoft 365 Certified' Enterprise Administrator Expert' certification. The MS-100 course is intended for individuals and teams who have some foundational knowledge of Microsoft 365 features and services. (If you are looking to form gain base knowledge of M365, check out our MS-900 M365 Fundamentals course). This course includes the following curriculum: - Introduction and Study Resources - Design and Implement M365 Services - Manage User Identity and Roles - Manage Access and Authentication - Plan Office 365 Workloads and Applications Lectures will educate you on the terms and principles of the M365 platform and demos will enable you with a hands-on experience using scenarios to empower you in the real world. Welcome to the Skylines Academy MS-100 course! We're happy you're joining us!"--Resource description page